MORPHOLOGIC AND ANATOMICAL FEATURES OF TYPE 1 MACULAR NEOVASCULARIZATION TRUNKS IN AGE-RELATED MACULAR DEGENERATION USING OPTICAL COHERENCE TOMOGRAPHY ANGIOGRAPHY. Issue 3 (March 2022) - Choi, Kwang-Eon; Kim, Seong-Woo; Yun, Cheolmin; Oh, Jaeryung
Abstract : Purpose: To evaluate the morphologic features of macular neovascularization (MNV) trunks at different layers using optical coherence tomography angiography. Methods: Type 1 MNV trunks in age-related macular degeneration were retrospectively evaluated at the subretinal pigment epithelium and sub-Bruch membrane (subBM) layers. The detectability and location of the trunks were compared. MNV trunks at the subBM layer on optical coherence tomography angiography B-scans were evaluated using a flow overlay. The correlations of the MNV trunk with optical coherence tomography angiography and optical coherence tomography parameters were evaluated. Results: Among the 63 included eyes, 27 showed core vessels at the subretinal pigment epithelium layer and 52 showed MNV trunks at the subBM layer, which were connected with the MNV at the subretinal pigment epithelium layer. The locations of the MNV trunks in each layer were different. MNV trunk types at the subBM layer were related to disease duration, distance from the large choroidal vessels, and MNV vessel density. The large choroidal vessel diameter was correlated with the MNV trunk diameter at the subBM layer. Conclusion: Macular neovascularization trunks at the subBM layer were detected more frequently than distal MNV trunks at the subretinal pigment epithelium layer. Macular neovascularization trunk features at the subBM layer may be related to disease duration and a large choroidal vessel. Abstract : Supplemental Digital Content is Available in the Text. Proximal macular neovascularization (MNV) trunks at the sub-Bruch membrane layer were detected more frequently than distal MNV trunks at the subretinal pigment epithelium layer. The subMNV large choroidal vessel diameter was related to the proximal MNV diameter, and the distal MNV trunk diameter was related to the MNV vessel density in the subretinal pigment epithelium layer.